Developing Web-Based Media for Teaching Writing Through Wordwall - Luluk Luluk Novia; Happy Kusuma Wardani; Alimin Alimin; Saleem Mohd Nasim (Departement of Mathematics Education, 2024)
The goal of this study is to develop web-based media for teaching writing through Wordwall. The seventh graders of SMP Nusantara Gresik served as the subject of this study. The five stages of the ADDIE approach for Research and Development (R&D) were employed for this study involving analysis, design, development, implementation, and evaluation. To ease the data collection, some instruments were utilized in the analysis stage and evaluation stage. The data in the analysis stage were collected through a questionnaire and an interview. Additionally, the data during the evaluation was collected through an observation sheet and questionnaire. The data was then analyzed descriptively. The final product of this study comprises three distinct Wordwall activities. Students; responses indicated positive reception of the developed Wordwall as a web-based media in teaching learning experience especially for writing activities.